A population-based comparison study of the mental health of patients with intentional and unintentional burns. Issue 1 (6th November 2018) - Vetrichevvel, Thirthar P; Randall, Sean M; Wood, Fiona M; Rea, Suzanne; Boyd, James H; Duke, Janine M
Abstract: Background: A number of studies report high prevalence of mental health conditions among burn patients. However there is a need to understand differences in the temporal relationship between mental health conditions and intentional and unintentional burns to hasten psychological prevention and intervention. This study aims to compare the socio-demographic profile, burn characteristics and pre- and post-burn psychiatric morbidity of burn patients by intent-of-injury. Methods: De-identified linked hospital, death and mental health (MH) case registry data of burn patients hospitalised in Western Australia between 1 January 1980 and 30 June 2012 were analysed. Crude (observed) post-burn rates of mental health admissions were generated by burn intent-of-injury. Descriptive statistics were performed to compare the characteristics of the burn patients. Results: A total of 30, 997 individuals were hospitalised for a first burn; 360 (1.2%) had self-harm burns and 206 (0.7%) assault burns. Over the study period, admission rates for assault burns increased by 4.8% per year (95% confidence interval (CI) 3.1–6.5%) and self-harm burns increased 6.9% per year (95% CI 4.8–9.1%). Self-harm and assault burns occurred mainly among those aged 15 to 44 years (median age, interquartile range (IQR): self-harm 30 years, 22–40; assault 31 years, 23–38). Those with self-harm burns had a longer index hospital stay (median (IQR): self-harm 15 days (5–35) vs 4 days (1–11) assault vs 4 days (1–10) unintentional) and higher in-hospital mortality (7.2% self-harm vs 1.9% assault burns vs 0.8% unintentional). More than half (55.0%) of self-harm burns had a prior hospitalisation (5-year lookback) for a MH condition vs 10.7% of assault burns and 2.8% of unintentional burns. Crude post-burn rates of MH admissions per 100 person-years (PY) by intent-of-burn subgroups: self-harm 209 per 100 PY, assault burns 11 per 100 PY and unintentional burns 3 per 100 PY. Conclusions: Intentional burn patients experienced significantly higher pre- and post-burn mental health morbidity along with significant adverse outcome in comparison with unintentional burns. Early psychological assessment and intervention could help in improving the MH of these patients.